The Role of Locust Bean and Ironwood Trees in Human Nutrition and Income in Nigeria - Tee, T.N.; Ogwuche, J.A.; Ikyaagba, E.T. (Pakistan Journal of Nutrition, 2009)
This study was conducted in North-Central Nigeria to access the role of African locust bean tree and Ironwood tree in the nutrition and income of the people in this area. Through focus group discussions with key informants and interviews held with 120 household heads, information on the contribution of the 2 tree species to households nutrition and income in the area were elicited between July, 2008 and February, 2009. Market survey of mean retail prices and operational costs of products from these trees were also recorded for analysis. Using Gross income and Total variable cost, Net incomes from each product was determined. The result revealed that both trees contributed significantly to the nutritional wellbeing of the people of North-Central Nigeria; and that their monthly net incomes from products of these trees compared favourably with the national minimum wage of N7500 (USD59 equivalence). Many of them were living above the national minimum wage. However, the sustainability of these benefits is threatened as these trees are being subjected to over exploitation and very limited efforts at establishing their plantations and maintaining their populations in the wild. The study therefore recommended improved harvesting and post-harvest techniques, intensive silvicultural research, and the establishment of plantations of these tree species in the area and beyond. Similarly, improved pricing policies and enhanced processing and marketing of products from these species for value addition are strongly recommended.